Erratum: Evaluation the relationship between body mass index and kinesiology band application to acute grip strength on healthy men (vol 24, pg 5, 2018) - Avcı, Ender Ersin; Altındağ, Özlem (European Journal of Therapeutics, 2018)
Erratum In the Turkish version of the article by Avcı and Altındağ, entitled “Evaluation the relationship between body mass index and kine-siology band application to acute grip strength on healthy men” (Eur J Ther 2018; 24(2): 5-11. DOI: 10.5152/EurJTher.2017.156) that was published in the March 2018 issue of European Journal of Therapeutics, some contextual errors has been detected. The specified corrections have since been implement on the online version of this article. • The title of Table 5 has been corrected. • The missing data in the Results section has been added. https://eurjther.com/index.php/home/article/view/311